Spliceostatin C, a component of a microbial bioherbicide, is a potent phytotoxin that inhibits the spliceosome - Bajsa-Hirschel, Joanna; Pan, Zhiqiang; Pandey, Pankaj; Asolkar, Ratnakar N.; Chittiboyina, Amar G.; Boddy, Louis; Machingura, Marylou C.; Duke, Stephen O. (Frontiers in Plant Science, 2023)
Spliceostatin C (SPC) is a component of a bioherbicide isolated from the soil bacterium Burkholderia rinojensis. The chemical structure of SPC closely resembles spliceostatin A (SPA) which was characterized as an anticancer agent and splicing inhibitor. SPC inhibited the growth of Arabidopsis thaliana seedlings with an IC50 value of 2.2 µM. The seedlings exposed to SPC displayed a significant response with decreased root length and number and inhibition of gravitropism. Reverse transcriptase semi-quantitative PCR (RT-sqPCR) analyses of 19 selected genes demonstrated the active impact of SPC on the quality and quantity of transcripts that underwent intron rearrangements such as intron retention as well as up or down expression upon exposure to SPC. Qualitative and quantitative proteomic profiles identified 66 proteins that were significantly affected by SPC treatment. Further proteomics data analysis revealed that spliceostatin C induces hormone-related responses in Arabidopsis seedlings. In silico binding studies showed that SPC binds to a pocket between the SF3B3 and PF5A of the spliceosome.